Genome analysis of the haloalkaliphilic bacterium Rhodobaca barguzinensis - Kopejtka, Karel (Jihočeská univerzita, 2019)
This PhD thesis presents results of a research focussed on the evolution of phototrophy in the bacterial order Rhodobacterales with a special regard to its haloalkaliphilic representatives. The photoheterotrophic bacterium Rhodobaca barguzinensis alga05 was used as an organism of choice. Its phylogeny, genome organization, and metabolic potential was characterized. The main result of the thesis is that phototrophy is a genuine trait among the haloalkaliphilic representatives of the Rhodobacter-Rhodobaca group inside the Rhodobacterales clade.
Genome analysis of the haloalkaliphilic bacterium Rhodobaca barguzinensis
Keywords: Anoxygenic photosynthesis; genome evolution; haloalkaliphiles; horizontal gene transfer; photosynthesis gene cluster; Rhodobacteraceae.; Anoxygenic photosynthesis; genome evolution; haloalkaliphiles; horizontal gene transfer; photosynthesis gene cluster; Rhodobacteraceae.